O fenômeno da terceirização no processo de precarização do trabalho contemporâneo - Almeida, Renata Coutinho de (2019)
This dissertation deals with the phenomenon of outsourcing as an instrument of the social precariousness process of contemporary labor. As a way to maintain the hegemony of the capitalist system, outsourcing is able to adapt to the volatilities of financial capitalism based on the exploitation of living labor and dismantle of social rights. Studies regarding economic and sociology of labor demonstrate that we are facing a productive dynamic that generates pulverization and subordination. It is a powerful tool for reducing labor costs by lowering wages, intensifying working hour, promoting invisibility and discrimination, the proliferation of illness and death at work and the fragmentation of the union structure. With the unrestricted outsourcing regulation, the so-called outsourcers tend to become a rule